Cartoon controversy: semiotic analysis of political cartoon by Zunar Portraying the issue of 1Malaysia Development Berhad (1MDB) / Syaza Marina Ramli and Mokhtar Muhammad - Ramli, Syaza Marina; Muhammad, Mokhtar (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2019)
As 1MDB rose into one of the most controversial issue in the political arena, a Malaysian cartoonist known as Zunar took the storm as well for constantly being arrested for a crime of provocative political drawings believed to mock the government and the leaders. The results of this study would provide insights into understanding the meanings and determine the real depictions behind his caricature drawings on the event of 1MDB. This study analyses the semiotic meanings behind the illustrations made by Zunar and the most prominent political cartoon elements he used in the illustration to portray the controversial political issue of 1MDB. The study employed a qualitative content analysis as the mode of the research. Two instruments namely coding sheets were used: an adopted standardised coding sheet designed by U.S. National Archives and Record Administration to analyse the cartoons – visual, words, and colour, and another coding sheet which was constructed based on standardised elements of political cartoons – symbolism, exaggeration, labelling, analogy, and irony – by Library of Congress and Abraham Lincoln Presidential Library Foundation. Results on the semiotic meanings of Zunar’s drawings on 1MDB issue showed that he was depicting the real-life events, and mocking political individuals involved accordingly to facts and news released several days before his cartoons were published. Most of his works contained elements of political cartoons without crossing rules that would sometimes were done excessively by other political cartoonists. Keywords: